MODEL PENGEMBANGAN ANDRAGOGIK DALAM MENUMBUHKAN SEMANGAT BERUSAHA JAMA’AH TAREKAT NAQSABANDIYAH JABAL QUBIS SUMATERA UTARA - Santoso, Didik; Daulay, Sholihatul Hamidah; Arlina, Arlina (UIN Sumatera Utara Medan, 2022)
This study aims at describing a model of andragogical development implemented by the leaders of Toriqoh Naqsabandiyah Jabal Qubis to empower their followers’ spirit to work. It is conducted at the non-formal institution of Naqsabandiyah Jabal Qubis by using phenomenological qualitative approach. The data of this research consist of the results of observation, deep interview, and focus group discussion. The data sources of this study are the top leader, the big chaliph, the old chaliph, and the young caliph. The data were analysed by the Miles, Huberman, and Saldana’s (2014) technique namely data condensation, data display, dan verification. The trustworthiness of this study is established through source and methodological triangulations. The findings of this research show that a model of andragogical development in empowering the followers’ spirit is applied through 4 steps : planning, developing, evaluating, doing follow-up, as well as their impacts.